Women, wrestling, and the Games: Olympic normalization of a practice (1996-2001) - Jomand, G.; Liotard, P.; Épron, A. (Staps, 2022)
A bastion of masculinities, wrestling offers a significant context for observing and analyzing the inequalities between men and women in sport. Examining the inclusion of women`s wrestling as an Olympic discipline in September 2001 helps to understand the hierarchy existing between wrestling styles and, consequently, between genders. Women`s wrestling was in fact constructed as a distinct style from the two styles for men, freestyle and Greco-Roman, and was based on the myth of women`s fragility. Analyzing the archives of the International Olympic Committee (IOC), the correspondence between the IOC and the International Federation of Associated Wrestling Styles (FILA), as well as the two organizations` meeting and commission reports, together with interviews of FILA stakeholders in the 1990s, shed light on the tensions and gender equality issues running through wrestling`s access to the Olympics. The entry of female wrestling into the Olympics shows the difficulties faced by FILA in breaking through the power system based on the hierarchy existing between the wrestling styles, within a context where the IOC held great power of persuasion, even constraint, and influenced the orientation of sporting policies, particularly from the perspective of greater equality.